1988
DOI: 10.1115/1.3250452
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Model of the Evaporating Meniscus

Abstract: Transport phenomena associated with the heating of a stationary fluid near saturation by an inclined, partially submerged copper plate were studied analytically. Under steady-state evaporation, the meniscus profile was derived using an appropriate liquid film velocity and temperature distribution in an integral approach similar to boundary layer analysis. Derivation of the meniscus profile led to predicting heat transfer and performance as a function of angle of inclination of the plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…It increases as the liquid pool is approached. , Mirzamoghadam and Catton (1988), and Wayner (1989) have examined the motion in the meniscus caused by the heat addition to the solid substrate. In order to prevent bulk or surface (Ast) nucleation, the solid surface temperature is maintained slightly above the saturation temperature.…”
Section: Cb) Dynamic Equilibriummentioning
confidence: 99%
See 1 more Smart Citation
“…It increases as the liquid pool is approached. , Mirzamoghadam and Catton (1988), and Wayner (1989) have examined the motion in the meniscus caused by the heat addition to the solid substrate. In order to prevent bulk or surface (Ast) nucleation, the solid surface temperature is maintained slightly above the saturation temperature.…”
Section: Cb) Dynamic Equilibriummentioning
confidence: 99%
“…slightly above the saturation temperature T. such that no boiling occurs. This problem has been studied by Bressler and Wyatt (1970), Wayner et al (1976), Wayner (1978), Holm and Goplen (1979), Cook et al (1981), , , Mirzamoghadam and Catton (1988), and . We begin by examining the heat transfer rate in the transition region (figure 11.2) and we include the capillary meniscus and liquid motion.…”
Section: Evaporation From Heated Liquid Filmmentioning
confidence: 99%
“…The first method is integrating the Clausius-Clapyron equation. Expanding the ClausiusClapeyron equation [5] dP dT…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Wayner et al [4] suggested the evaporative mass flux as a function of temperature and pressure at the interface based on Kelvin-Clapeyron equations. Mirzamoghadam and Catton [5] used an appropriate liquid velocity and temperature distribution in an integral approach similar to boundary layer analysis to obtain the evaporating meniscus profile. Stephan and Busse [6] concluded that the assumption of liquid-vapor interface temperature equal to the saturation temperature of vapor can lead to a large overprediction of the radial heat transfer coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1972, Potash and Wayner (1972) expanded the Derjaguin-LandauVerwey-Overbeek (DLVO) theory (Derjaguin and Zorin 1956) to describe evaporation and fluid flow from an extended meniscus. Following this work, extensive investigations (Wayner et al 1976;Moosman and Homsy 1980;Holm and Goplen 1979;Mirzamoghadam and Catton 1988;Burelbach et al 1988;Stephan and Busse 1993;Ma and Peterson 1997;Demsky and Ma 2004;Ma et al 2008) have been conducted to further understand mechanisms of fluid flow coupled with evaporating heat transfer in thin film region. In this section, the disjoining pressure is introduced first, then the pressure across the liquid-vapor interface is tracked followed by a discussion of thin film profile, interface temperature, and heat transfer through the thin film region.…”
Section: Thin Film Evaporationmentioning
confidence: 99%